The hidden dangers of falsified and substandard medicines: Developing countries are most affected by the illegal trade - Judith Vorrath; Maike Voss (Stiftung Wissenschaft und Politik (SWP), 2019)
When talking about health risks in developing countries, many people think of events such as the Ebola virus epidemic in 2014 and 2015 in West Africa. The effects of trade in falsified and substandard medicines are far less known. Developing countries are particularly affected since they are easy targets for the illegal trade due to insufficient regulations and controls as well as limited access to health care. The health and (socio-)economic consequences are severe. Moreover, criminal networks make large profits, usually without having to fear any significant punishment. The German government can push for a stronger focus on the issue at the World Health Assembly in May 2019. Germany's bilateral engagement should, above all, support developing countries in making drug supply chains safer.
Keywords: 320